Acute response to rapid iloprost inhalation using the Breelib™ nebulizer in pulmonary arterial hypertension: the Breelib™ acute study. (1st September 2019) - Richter, Manuel J.; Wan, Jun; Ghofrani, Hossein A.; Seeger, Werner; Gall, Henning; Rieth, Andreas; Tello, Khodr
Abstract : The Breelib™ nebulizer was designed to reduce iloprost inhalation times for patients with pulmonary arterial hypertension (PAH). In 30 patients with PAH, rapid inhalation of iloprost 2.5 µg using Breelib™ caused significant improvements in invasively measured afterload and cardiac index but not echocardiographic right ventricular strain during 30 min post‐inhalation.